Calcium peroxide and freezing co-pretreatment enhancing short-chain fatty acids production from waste activated sludge towards carbon–neutral sludge treatment. (January 2023) - Zhao, Weixin; You, Jia; Yin, Shilei; He, Shufei; Feng, Likui; Li, Jianju; Zhao, Qingliang; Wei, Liangliang
Graphical abstract: Highlights: CaO2 and freezing co-pretreatment remarkably improved SCFAs yields from WAS. Maximal SCFAs yield of 438.5 mg COD/g VSS was achieved by co-pretreatment. Co-pretreatment facilitated the WAS disintegration and promoted organics released. Co-pretreatment enriched hydrolytic and acetogenic microbes, inhibited methanogens. Co-pretreatment exhibited obvious economic and carbon-emission reduction benefits. Abstract: Short-chain fatty acids (SCFAs) recovery through anaerobic fermentation is a promising technology to achieve carbon–neutral in waste activated sludge (WAS) management. After 0.15 g CaO2 /g volatile suspended solids (VSS) addition and three-cycle freezing co-pretreatments, the maximal SCFAs production of 438.5 mg COD/g VSS was achieved within 4 days fermentation, and more than 70 % of SCFAs was composed of acetate and propionate, which achieved a higher level than reported in previous studies. Mechanism explorations elucidated that co-pretreatment triggered sludge solubilization, promoting the release of biodegradable organics, providing more biodegradable substrates for SCFAs generation. Further microbial community analysis indicated that the abundances of hydrolytic microorganisms and acidogens were enriched, whereas methanogens were inhibited. Besides, environmental analysis suggested that co-pretreatment could achieve carbon reduction benefits of 0.116–0.291 ton CO2 /ton WAS, demonstrating its huge carbon–neutral potential benefits.